Implementasi Blockchain pada Peer-to-Peer Transaction menggunakan Algoritma U-Quark - Gibran Akbaromi Luhkito; Ari Kusyanti; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Blockchain is a database system that has a decentralized architecture, where every data contained in the blockchain system is spread across all peers that are connected in the blockchain system. One of the most discussed blockchain uses is cryptocurrency, which was coined by Bitcoin. In the hashing process on the blockchain system used by Bitcoin using the SHA-256 algorithm, a weakness has been found of the SHA-256 algorithm, namely the preimage attack using the biclique concept on the compression function owned by SHA-256. This is what underlies the author to implement blockchain in peer-to-peer transactions using the U-Quark algorithm. The author uses the U-Quark algorithm because the architecture owned by the Quark Family hashing uses a combination of block ciphers and stream ciphers owned by Katan and Grain for permutations and uses Sponge Construction as its constructor. There are 3 factors tested in this study, namely test vectors, functional, and availability. In vector testing, the resulting digest value is the same between the implemented U-Quark algorithm and the digest value that has been determined in the hashing family Quark. In functional testing using the blackbox method with 100% valid results. The Availability tester generates the same data in every peer available in the blockchain system. The U-Quark algorithm consists of 3 stages, namely the initialization phase, the absorbing phase, the squeezing phase, and the blockchain system built involves 2 types of systems, namely the blockchain system and the wallet system. The blockchain system functions as a storage system and a wallet system as a place to enter transactions into the blockchain system.